(untitled) (Medical Forum Monthly, 2024)
Objective: The stroke is leading cause of death in world and many patients die of an acute stroke. This study was conducted to determine whether the hypertension is independent risk factor for acute stroke. Study Design: Prospective cross sectional Place and Duration of study: This study was carried out at AK CMH/SKBZ Muzaffarabad from May 2012 to May 2013. Materials and Methods: In this study 220 patients having first ever acute stroke. Many clinical variables have been investigated as risks factors for stroke.The hypertension was investigated as a risk factor for stroke. The evaluation of patients included structured questionnaire, clinical, neurological examinations, laboratory tests, and computed tomogram scan (CT) brain. The follow-up at 14 days was done for all patients. Results: Out of 220 cases of acute stroke, 171 (77.73%) were hypertensive, and 49(22.27) % were normotensive. The statistical significant risk factors for stroke were: hypertension (p=0.04) and Hypercholesterolemia (p=0.05); for cerebral infarction (CI): (p=<0.001) and hypertension (p = 0.05) and Hypercholesterolemia (p=0.001); for intracerebral hemorrhagic (ICH) stroke (p = <0.001). The low Glasgow coma scale (GCS) score (p=0.05) on admission was associated with high mortality and worst outcome in hypertensive patients. Thus hypertension has statistical significant association for both CI and ICH stroke patients. Conclusion: This study confirms the statistical significant association of hypertension with acute stroke and emphasizes the need in preventing and controlling of hypertension in order to avoid stroke and its mortality.